2014
DOI: 10.1016/j.maturitas.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative cross-cultural exploration of vaginal bleeding/spotting symptoms and impacts associated with hormone therapy in post-menopausal women to inform the development of new patient-reported measurement tools

Abstract: Women taking EPT in the US, China, Mexico and Italy reported vaginal bleeding/spotting symptoms that have a detrimental impact on their quality of life. Two new measures were developed to assess the severity and impact of vaginal bleeding/spotting specific to EPT. This work highlights the need for EPT-related symptoms to be a part of treatment decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Among individuals who reported vulvovaginal symptoms, CI and CASI survey modes were moderately concordant. In contrast to previous studies which found CASI had a higher frequency of responses (albeit to questions on sexual behaviors [18][19][20][21][22][23][24][25] and menstruation, [26][27][28] rather than specific vulvovaginal symptoms), we found CI resulted in slightly more responses than CASI, although the differences were not statistically significant. Our findings also indicated that when a participant reported not having symptoms on CASI, they were likely to indicate no symptoms to CI, and thus, concordance between interview modes was high because of the large majority with negative reporting.…”
Section: Discussioncontrasting
confidence: 99%
“…Among individuals who reported vulvovaginal symptoms, CI and CASI survey modes were moderately concordant. In contrast to previous studies which found CASI had a higher frequency of responses (albeit to questions on sexual behaviors [18][19][20][21][22][23][24][25] and menstruation, [26][27][28] rather than specific vulvovaginal symptoms), we found CI resulted in slightly more responses than CASI, although the differences were not statistically significant. Our findings also indicated that when a participant reported not having symptoms on CASI, they were likely to indicate no symptoms to CI, and thus, concordance between interview modes was high because of the large majority with negative reporting.…”
Section: Discussioncontrasting
confidence: 99%
“…Many women with bothersome VMS remain untreated or use nonprescription medications, herbal supplements or alternative therapies [15][16][17]. Factors influencing treatment decisions include safety and tolerability (e.g., breast cancer, stroke, venous thromboembolism, breast tenderness, vaginal bleeding) related to long-term HT use [18][19][20][21][22] and moderate efficacy of non-hormonal treatments [10]. Although previous studies have examined the burden of VMS associated with menopause [7,8], a more comprehensive understanding of VMS burden and patient/physician perspectives on its management is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about long-term safety of hormone therapy and moderate efficacy of available nonhormone treatment for VMS may be contributing to low usage rates of these therapies. [45][46][47][48][49][50] Therefore, new therapies that are safe and effective in reducing hot flashes and night sweats could be beneficial in improving sleep quality among women with VMS.…”
Section: Depree Et Almentioning
confidence: 99%